2020
DOI: 10.17759/bppe.2020170103
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Pedagogical Helping to Preschoolers Using the Methods of Psychotechnics Based on the Movements

Abstract: The article describes the conditions for the active development of psychological and pedagogical assistance to children 3–7 years old in Russian preschool institutions, the beginning of the using of movement-based psychotechnics in working with preschool children. The problem is formulated as the need to search and develop methods of psychological and pedagogical assistance to preschool children, which use motor tasks that “work” to identify and overcome difficulties in developing communication, arbitrariness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Based on Wilcoxon rank sum test, the statistical analysis demonstrated the significant differences between the first and second psychodiagnostic studies of the indicators of volume and stability of voluntary attention in both control (z = 4.622599, p-value = 0.000004) and experimental (z = 3.919930, p-value = 0.000089) groups. Information on the positive effect of the "Brain jogging" technique in the scientific literature is available only for children with special needs and general speech underdevelopment [25]. Our study showed that this psycho-gymnastics can also be used in the rehabilitation of CVA patients.…”
Section: Discussionmentioning
confidence: 70%
“…Based on Wilcoxon rank sum test, the statistical analysis demonstrated the significant differences between the first and second psychodiagnostic studies of the indicators of volume and stability of voluntary attention in both control (z = 4.622599, p-value = 0.000004) and experimental (z = 3.919930, p-value = 0.000089) groups. Information on the positive effect of the "Brain jogging" technique in the scientific literature is available only for children with special needs and general speech underdevelopment [25]. Our study showed that this psycho-gymnastics can also be used in the rehabilitation of CVA patients.…”
Section: Discussionmentioning
confidence: 70%